2010
DOI: 10.1007/s00432-010-0868-x
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive approach leads to improved survival in hepatocellular carcinoma patients with portal vein tumor thrombus

Abstract: PurposeMany physicians express a relatively nihilistic approach to the treatment of hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT). Consensus among surgeons regarding the indications for an aggressive approach has not been reached. Current study was aimed to determine whether an aggressive approach, with an extended resection with thrombectomy and adjuvant therapy, would lead to an improved survival for HCC patients with PVTT.MethodsA retrospective review of 116 HCC patients with PVTT ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…The presence of PVTT in patients with HCC is one of the most significant factors for a poor prognosis in developing countries (Lin et al, 2010; Shi et al, 2010). Once PVTT is formed, the tumor cells may spread along the portal vein, leading to extensive bilobar intrahepatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PVTT in patients with HCC is one of the most significant factors for a poor prognosis in developing countries (Lin et al, 2010; Shi et al, 2010). Once PVTT is formed, the tumor cells may spread along the portal vein, leading to extensive bilobar intrahepatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…If untreated, the prognosis of patients with HCC and PVTT becomes extremely poor [4]. The median survival of patients with HCC and PVTT is 2.7–4.0 months, whereas survival in patients with HCC but without PVTT is 24.4 months [57]. For these patients, there is no effective treatment and the optimal treatment remains controversial [3].…”
Section: Introductionmentioning
confidence: 99%
“…As surgical techniques and treatment in general of HCC have improved, survival outcomes have also improved. For successive 5-year periods (1996-2000 vs. 2001-2006), Lin et al [15 ]reported median survivals for patients who had hepatic resection and thrombectomy of 21 and 36 months, respectively (p < 0.001) despite a tendency for patients in the later cohort to have more advanced disease. The location and extent of PVTT also significantly affect the potential survival outcomes following surgery [9].…”
Section: Surgical Optionsmentioning
confidence: 99%
“…The location and extent of PVTT also significantly affect the potential survival outcomes following surgery [9]. Various series have found that patients with PVTT extending to the main trunk of the portal vein or beyond have poorer outcomes after surgery compared to those with PVTT confined to the first- or second-order portal branches (table 1) [9,13,14,15]. …”
Section: Surgical Optionsmentioning
confidence: 99%